Perancangan Aplikasi E-Learning Berbasis Website Pada SMP Negeri 3 Watansoppeng - Riska Handayani; Zul Rachmat; Wahyuddin S (STMIK Amika Soppeng, 2022)
ABSTRACT Education is one of the benchmarks in the progress of the nation. Educational progress affects science and technology. E-Learning is a form of education that combines motivation, communication, efficiency and technology. E- Learning is an educational system that uses electronic applications to support the development of teaching and learning activities with internet media. This study aims to design a web-based E-Learning application in schools. SMP Negeri 3 Watangsoppeng is one of the menegah schools located in Soppeng Regency where the learning process is still conventional, namely the teaching and learning process between teachers and students is only carried out by meeting between teachers and students in the classroom. The research methods carried out are observation, interviews, and literature studies. Research is carried out by analyzing objects that are used as research sources, research using waterfall methods in the development of the system consisting of system analysis, designing, coding, testing and maintenance. Application design using UML and application creation using PHP as Script material used to create website pages and Mysql as a place to store data. The results of this study aim to show that this website-based E-Learning Application is able to increase the effectiveness of learning and optimize the teaching and learning process between students and teaching staff at SMP Negeri 3 Watansoppeng.